Do Consumers Evaluate New and Existing Fruit Varieties in the Same Way? Modeling the Role of Search and Experience Intrinsic Attributes. Issue 8 (12th October 2020) - Uribe, Rodrigo; Infante, Rodrigo; Kusch, Carolina; Contador, Loreto; Pacheco, Igor; Mesa, Karen
ABSTRACT: Studies have demonstrated the significance of intrinsic sensory attributes on consumer responses to fruits. This paper evaluates the effects on consumers of intrinsic characteristics on new and existing fruit varieties. Fruit consumers were exposed to and tasted a new or an old variety of fruit and rated its intrinsic search and experience attributes, as well as their satisfaction and purchase intention. Results indicated, firstly, that search and experience intrinsic attributes significantly predicted satisfaction and purchase intention. Secondly, the examination of differences between existing and new varieties showed not only a general similarity but also some differences: search attributes played a more relevant role in the purchase intention among existing varieties, and experience qualities were more important for new varieties in terms of satisfaction. It was observed that new varieties were preferred over existing ones. Results are discussed in terms of their implications for consumer behavior study and for managers.